2013
DOI: 10.1007/s12011-013-9751-3
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Aluminum Concentration Does Not Affect the Genomic Stability of ERBB2, C-MYC, and CCND1 Genes in Breast Cancer

Abstract: It has long been hypothesized that body tissue uptake of aluminum may have biological implications in breast cancer. In vitro and in vivo studies have shown that aluminum may trigger genomic instability by interfering with DNA strands. The objective of this study was to examine the relationship between aluminum concentrations in the peripheral and central areas of breast tumors with the instability of three key genes in breast cancer, ERBB2, C-MYC, and CCND1 and aneuploidy of the chromosomes harboring these ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The metals that change the oestrogen hormone level are called metalloestrogen. The unwanted oestrogenic effects of aluminium, such as altered protein expression, change in puberty signs and tumour development, may be seen (House et al, 2013; Mandriota et al, 2016; Mannello et al, 2013; Pineau et al, 2014; Rodrigues‐Peres et al, 2013a, 2013b; Wallace, 2015). Overall metalloestrogenic effects of aluminium may potentiate the breast's changes (Darbre, 2009; Darbre, Mannello, & Exley, 2013; Wallace, 2015).…”
Section: Aluminium and Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…The metals that change the oestrogen hormone level are called metalloestrogen. The unwanted oestrogenic effects of aluminium, such as altered protein expression, change in puberty signs and tumour development, may be seen (House et al, 2013; Mandriota et al, 2016; Mannello et al, 2013; Pineau et al, 2014; Rodrigues‐Peres et al, 2013a, 2013b; Wallace, 2015). Overall metalloestrogenic effects of aluminium may potentiate the breast's changes (Darbre, 2009; Darbre, Mannello, & Exley, 2013; Wallace, 2015).…”
Section: Aluminium and Breast Cancermentioning
confidence: 99%
“…Rodrigues‐Peres et al (2013b) measured aluminium concentration in central and peripheral parts of breast tumours. They found no significant difference between aluminium concentration in the tumour and the healthy tissue around the tumour.…”
Section: Aluminium and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cadmium reportedly induces DNA fragmentation and tumorigenesis, but not the expression of genes such as bcl-x or MT-1 in Wistar rat testis and prostate [90]. Rodrigues-Peres et al [91] found no ERBB2, C-MYC, and CCND1 gene instability when assessing the correlation between aluminum and genomic instability in cancerous human breast tissues and healthy tissues. Additionally, as previously reported, the changes were observed at extremely low or nanomolar concentrations of aluminum, with the ability to induce the expression of pro-inflammatory and pro-apoptotic genes.…”
Section: Genetic Expression Assay Using Rt-qpcrmentioning
confidence: 99%
“…We performed a secondary analysis of data collected from other studies linked to our study group. [8][9][10][11][12] The principal investigator (Juliana Pinho Espinola -JPE) conducted a further review of 226 medical records, specifically for the present report, in order to obtain data regarding clinical staging, exams, and pathological staging. Clinical and epidemiological data are from January 2008 to September 2010.…”
Section: Methodsmentioning
confidence: 99%